Is CAD A Good Paradigm for MBSE?. Issue 1 (20th September 2021) - Henderson, Kaitlin; Salado, Alejandro
Abstract: Those looking to advocate for Model‐Based Systems Engineering (MBSE) in the Systems Engineering field often turn to more established fields that have made a similar transition to models to assure others it will be beneficial. One practice that is often compared to MBSE is Computer‐Aided Design (CAD) from the field of mechanical engineering. However, the adequacy of this comparison is challenged upon a side‐by‐side examination of what MBSE and CAD are. Based on the established definitions, it is evident that while CAD can be considered a method of mechanical drawing, MBSE cannot be described as only a method. MBSE is more than installing and utilizing software, it is a process in and of itself. Comparing MBSE to CAD runs the risk of oversimplifying MBSE and setting up expectations that may not be met. Therefore, while CAD may represent a similar paradigm shift as MBSE in terms of digitalization, it may not serve as an adequate paradigm in terms of adoption and benefits. In this paper, we characterize and compare CAD and MBSE and identify the similarities and differences between them. We use the resulting insights to level the expectations of adopting and using MBSE.